Visual memory and psychotic symptoms in youth. Issue 3 (3rd May 2020) - Howes Vallis, Emily; MacKenzie, Lynn E.; Zwicker, Alyson; Drobinin, Vladislav; Rempel, Sheri; Abidi, Sabina; Lovas, David; Bagnell, Alexa; Propper, Lukas; Omisade, Antonina; Fisher, Helen L.; Pavlova, Barbara; et al.
ABSTRACT: Background: Psychotic symptoms are common during childhood and adolescence and may indicate transdiagnostic risk of future psychiatric disorders. Lower visual memory ability has been suggested as a potential indicator of future risk of mental illness. The relationship between visual memory and clinician-confirmed definite psychotic symptoms in youth has not yet been explored. Methods: We examined visual memory and psychotic symptoms among 205 participants aged 7–27 years in a cohort enriched for parental mood and psychotic disorders. We assessed visual memory using the Rey Complex Figure Test (RCFT) and psychotic symptoms using validated semi-structured interview measures. We tested the relationship between visual memory and psychotic symptoms using mixed-effects logistic regression. Results: After accounting for age, sex, and family clustering, we found that psychotic symptoms were significantly associated with lower visual memory (OR = 1.80, 95% CI 1.06–3.06, p  = 0.030). This result was unchanged after accounting for general cognitive ability. Conclusion: Lower visual memory performance is associated with psychotic symptoms among youth, regardless of general cognitive ability. This finding may inform future targeted early interventions.